Arginine side chain interactions and the role of arginine as a gating charge carrier in voltage sensitive ion channels - Armstrong, Craig T; Mason, Philip E; Anderson, J L Ross; Dempsey, Christopher E (Scientific reports, 2016)
Gating charges in voltage-sensing domains (VSD) of voltage-sensitive ion channels and enzymes are carried on arginine side chains rather than lysine. This arginine preference may result from the unique hydration properties of the side chain guanidinium group which facilitates its movement through a hydrophobic plug that seals the center of the VSD, as suggested by molecular dynamics simulations. To test for side chain interactions implicit in this model we inspected interactions of the side chains of arginine and lysine with each of the 19 non-glycine amino acids in proteins in the protein data bank. The arginine guanidinium interacts with non-polar aromatic and aliphatic side chains above and below the guanidinium plane while hydrogen bonding with polar side chains is restricted to in-plane positions. In contrast, non-polar side chains interact largely with the aliphatic part of the lysine side chain. The hydration properties of arginine and lysine are strongly reflected in their respective interactions with non-polar and polar side chains as observed in protein structures and in molecular dynamics simulations, and likely underlie the preference for arginine as a mobile charge carrier in VSD.
Keywords: Animals; Molecular Dynamics Simulation; ERG1 Potassium Channel; databáze proteinů; Lysine; lysin; vodíková vazba; Hydrophobic and Hydrophilic Interactions; statická elektřina; sekvence aminokyselin; Arginine; Structure-Activity Relationship; lidé; simulace molekulární dynamiky; draslíkový kanál ERG1; strukturní homologie proteinů; Amino Acid Sequence; Ion Channel Gating; guanidin; voda; gating iontového kanálu; Guanidine; Water; Structural Homology, Protein; Databases, Protein; Protein Isoforms; Hydrogen Bonding; arginin; vztahy mezi strukturou a aktivitou; protein - isoformy; zvířata; Static Electricity; hydrofobní a hydrofilní interakce; Humans